2019
DOI: 10.1177/1071100719867932
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Weightbearing Following Open Reduction and Internal Fixation of Unstable Ankle Fractures on Wound Complications or Failures of Fixation

Abstract: Background: There is a growing trend toward early weightbearing as tolerated (WBAT) after open reduction and internal fixation (ORIF) of ankle fractures. To date, studies have excluded fractures with associated syndesmotic injuries from their cohorts. Methods: In this retrospective cohort study, a chart review was performed at a single level 1 trauma center, identifying all unstable ankle fractures that underwent operative fixation between July 2016 and July 2017. After exclusion criteria, 63 patients were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
(14 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, there were no differences noted in postoperative weightbearing restrictions or documented weightbearing compliance (Supplemental Table 2a-d). This tracks with a recent investigation by Pyle et al, 43 who found that early weightbearing (2-4 weeks postoperatively) after unstable ankle fracture ORIF with or without syndesmotic injury did not increase the risk of wound complications or failure of fixation among their cohort of 31 patients. Notably, surgeon fellowship training had no correlation with an increased need for revision.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, there were no differences noted in postoperative weightbearing restrictions or documented weightbearing compliance (Supplemental Table 2a-d). This tracks with a recent investigation by Pyle et al, 43 who found that early weightbearing (2-4 weeks postoperatively) after unstable ankle fracture ORIF with or without syndesmotic injury did not increase the risk of wound complications or failure of fixation among their cohort of 31 patients. Notably, surgeon fellowship training had no correlation with an increased need for revision.…”
Section: Discussionsupporting
confidence: 86%
“…Foreign scholars proposed 12 , 13 that early weight bearing in postoperative ankle fracture patients can help accelerate fracture healing, and early postoperative weight bearing will not lead to problems such as loosening of internal fixation, and it is believed that early weight bearing training is advantageous for ankle joint function recovery and fracture healing. Some scholars have confirmed 14 that early weight-bearing is beneficial to fracture healing, shortens fracture healing time, and promotes the recovery of joint function.The results of this study showed that early standing bed participation in weight-bearing training, and anti-gravity running table training intervention for 8 weeks after the increase in bone mineral density, the quality of bone scab score is higher than that of the control group who received conventional treatment, and there is no displacement of the fracture broken end and the phenomenon of loosening of the internal fixation, which suggests that early progressive weight-bearing can help to accelerate the healing of the fracture, which may be related to the stress stimulation of the fracture broken end, which is in line with the previous research findings Consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Immobilization, on the other hand, can be linked to a reduced range of motion, ankle stiffening, and muscular weakness [14]. Early mobility, on either hand, is thought to be critical for most fractures' healing, as well as minimizing joint stiffness and problems associated with extended immobilization, which may also help to speed up recovery and enhance overall function and quality of life [15]. Joint manipulation, gradual exercise performance, gait training plan, electrotherapy, and good health education have all been demonstrated to be useful in physiotherapy rehabilitation [16,17].…”
Section: Postoperativementioning
confidence: 99%